Smoothed Particle Hydrodynamics (SPH) method for modelling 2-dimensional free surface hydrodynamics - Ramli, Muhammad Zahir; Temarel, Pandeli; Mingyi, Tan (CRC Press, 2015)
The main goal of the current research is to implement Smoothed Particle Hydrodynamics (SPH) for the prediction of wave-induced motions and loads within the framework of 3D modelling. In this paper, the focus is twofold. First, implementation of possible additional terms to the standard incompressible SPH (ISPH) method with reference to generating/propagating regular waves in 2D domain, using a piston wave maker. Improvements to the prediction of pressure and velocity fields are then carried out with kernel renormalization technique and shifting technique without increasing the computational cost. The arc method is employed to improve the accuracy of free surface recognition, i.e. “noise-free” free surface. In addition, the weakly compressible (WCSPH) is also applied to the problem of 2D regular wave generation. Comparisons of predicted free surfaces, their kinematic and dynamic characteristics between ISPH, WCSPH and analytical so-lutions for a range of frequencies are carried out. The second focus of the paper is the 2D radiation problem due to forced sinusoidal oscillation of a rectangular section floating on calm water. The predicted hydrody-namic actions and coefficients in sway by WCSPH are then compared against available experimental meas-urements.